The Role of Gamification in Enhancing Student Engagement in Grades 4-6: A Systematic Literature Review - Setria Utama Rizal; Muhammad Syabrina (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to examine the role of gamification in increasing the cognitive engagement of elementary school students in grades 4-6 in general learning contexts. Using a systematic literature review approach, this research analyzes various studies from indexed journals that discuss the impact of gamification elements, such as points, leaderboards, and challenges, on student motivation and engagement. The review results show that gamification consistently increases cognitive engagement, primarily through increasing intrinsic motivation and adapting to students' learning styles. In addition, teachers play an important role in the successful implementation of gamification in the classroom. However, these findings also demonstrate the limitations of the Indonesian educational context and the lack of longitudinal research on the long-term effects of gamification. Therefore, further research is needed to assess the effectiveness of gamification in the long term and in national educational contexts. Practical implications of this research include the integration of gamification in curriculum and teacher training for more effective implementation. This research makes a significant contribution to the understanding of how gamification can be applied to improve the quality of learning at the primary school level.